2018
DOI: 10.1016/j.btre.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biochemical characterization of an Aspergillus niger phytase produced by solid-state fermentation using triticale residues as substrate

Abstract: HighlightsExtracellular phytase from A. niger has attractive biochemical properties as an animal feed additiveA new biocatalyst was high thermostability and resistance to acidic pHvalues was produced and purified.Phytase was as able to hydrolyze a large number of phosphate substrates, with high yields.A great variety of metal ions showed to have a beneficent effect on the enzyme, significantly increasing its catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…Purification procedure applied in the current report recorded a 23-fold increase in the specific activity of phytase, like the other published work (Casey and Walsh 2003; Neira-Vielma et al 2018; Monteiro et al 2015). Interference by contaminant proteins was undetectable and partially purified enzyme was sufficient for studying stability parameters.…”
Section: Discussionsupporting
confidence: 84%
“…Purification procedure applied in the current report recorded a 23-fold increase in the specific activity of phytase, like the other published work (Casey and Walsh 2003; Neira-Vielma et al 2018; Monteiro et al 2015). Interference by contaminant proteins was undetectable and partially purified enzyme was sufficient for studying stability parameters.…”
Section: Discussionsupporting
confidence: 84%
“…The bioprocess for phytase production by fungi, especially within the genera Aspergillus , Mucor , Penicillium , Rhizopus , and Thermomyces , using different agricultural residues had been previously studied and reported on by a number of researchers [ 20 , 21 , 23 , 24 , 32 , 33 , 34 , 35 , 36 , 37 ]. Nevertheless, only a limited number of published reports are available with regard to the production of phytase obtained from mushroom cultures using agricultural residue through SSF.…”
Section: Discussionmentioning
confidence: 99%
“…However, some previous studies have reported that the optimal temperature for the phytase activity of several Aspergillus species, Ceriporia sp. CBS 100231, Mucor hiemalis , Peniophora lycii CBS 686.96, and Penicillium simplicissimum W46 was 55 °C [ 35 , 73 , 74 , 75 , 76 ]. Studies on phytase activity involving A. niger ATCC 9142 [ 77 ] and A. ficuum NTG−23 [ 78 ] indicated that the optimal temperatures were 65 and 67 °C, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of fungal fermentation to enhance nutritional properties like fiber and protein content have been also reported ( Table 1). For instance, diverse Aspergillus species have been used to produce fungal enzymes with important technological applications, such as xylanases through brewer's spent grain fermentation (Beg et al, 2001); phytases through fermentation of triticale residues (Neira-Vielma et al, 2018), α-amylases through fermentation of soya, wheat bran and other starchy residues (Mathew et al, 2016;Melnichuk et al, 2020), proteases through fermentation of soya bean and wheat bran (Novelli et al, 2015), or lipases through fermentation of lipid-rich agro-wastes such as olive pomaces (Oliveira et al, 2016). Of technological interest is also the production of natural pigments, such as the ones produced by the fermentation of rice pasta with Monascus purpureus, a process which also results in the production of an anti-hypercholesterolaemic agent (Jirasatid et al, 2019).…”
Section: Fermentation Processes Employing Fungi and Yeastsmentioning
confidence: 99%